Promoting EFL students' oral proficiency through the implementation of English Movies: A quasi-experimental research at Indonesia high school - Alka, Nur Faiza Harsono; Thamrin, Nur Sehang; Wahyudin, Wahyudin (Research and Social Study Institute, 2024)
This study investigates the impact of utilizing English Movies as a learning aid on students' oral proficiency in senior high schools in Indonesia. The research is an experimental study with a quasi-experimental design in a senior high school in Central Sulawesi, Indonesia. The research population consisted of all students of the Grade XI Science class. However, only two classes were selected purposively as the research samples: the Grade XI Science 1 class as an experimental group and the Grade XI Science 2 class as a control group. The number of the students were 22 and 24 respectively. With a probability value (p) for students' oral competency of p < 0.05, the research findings demonstrate a strong impact of learning aided by English movies on speaking abilities. In addition, the average score of students who utilized English Movies to enhance their speaking skills had a significant impact of 51.8182 compared to their counterparts in the control group, with an average score of 36.6667. In conclusion, the utilization of English Movies as a learning tool has a positive impact on promoting students' oral proficiency.